PENGARUH GENDER, PENGHARGAAN FINANSIAL DAN PERTIMBANGAN PASAR KERJA TERHADAP MINAT MAHASISWA AKUNTANSI UNTUK BERKARIR MENJADI AKUNTAN PUBLIK DAN NON AKUNTAN PUBLIK - Astri Wulan Dary; Fitrawati Ilyas (UNIB Press, 2017)
The aim of this research is to examine and analyze the Influence of Gender, Financial Reward and Job Market considerations on intention of Accounting Students in Bengkulu City to have a career become Public Accountant and Non Public Accountant. This research is empirical research with quantitative approach which involves the use of statistical analysis. This research is using the primary data. Samples in this research consist of 160 accounting students of 1 public and 3 private Universities in Bengkulu City. The tool used in this research is logistic regression with SPSS software version 16. This study found that gender affect on the accounting students intention in Bengkulu City to have a career become public accountant and non public accountant, but financial reward and job market considerations this could not provide empirical evidence on the accounting students interest in bengkulu city to have a career become public accountant and non public accountant.Keywords : Gender, Financial Reward and Job Market Considerations. The Interest to have a career become Public Accountant and Non Public Accountant